Reducing Perioperative Anxiety and Postoperative Discomfort in Children With Hypnosis Before Tonsillotomy and Adenoidectomy: A Prospective Randomized Trial - Barbara Schmidt; Claudia Thomas; Antje Göttermann; Winfried Meißner; Katharina Geißler; Orlando Guntinas‐Lichius; Anne Schirrmeister (Health Science Reports)
ABSTRACT Background and Aims Children undergoing tonsillotomy (TT) or adenoidectomy (AT) often suffer from anxiety before and pain or nausea afterward. Greater preoperative anxiety in children and their parents is associated with increased postoperative discomfort. The aim of our study is to test if a preoperative hypnosis intervention reduces perioperative anxiety and thereby alleviates postoperative discomfort. Methods In a previous study, we developed a narcosis comic to reduce children's preoperative anxiety. Now, we investigate whether a hypnosis audio intervention further reduces children's perioperative anxiety. Here, a little monkey describes the surgery as an adventurous space journey. We included children 3−6 years old receiving TT or AT. Thirty‐four children prepared for the surgery with the hypnosis audio intervention in addition to the comic (comic+hypnosis group), while 30 children received the comic only (comic group). All children received preoperative sedation via midazolam. We measured children's subjective well‐being before and after surgery, parents' anxiety before surgery, children's anxiety during surgery, and children's postoperative pain. Results Children showed high well‐being before and after surgery in both groups with subjective distress ratings around 2 out of 10. Parents' anxiety was on a moderate level in both groups with anxiety ratings around 42 on the STAI‐S scale from 20 to 80. Children's anxiety was low to moderate in both groups during surgery with mYPAS ratings of 33 on a scale from 20 to 100. In the postoperative telephone interviews, children reported medium pain ratings with maximum pain values around 5 out of 10 in both groups with no significant differences in any postoperative outcome between groups. Conclusion Our study shows that all children participating in our study reported high well‐being and low anxiety. In future studies, it should be assessed if the combination of nonmedical interventions like narcosis comic and hypnosis shows an additive effect in non‐medicated children.